2019
DOI: 10.1186/s12886-019-1057-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age-related cataracts on colour perception, postoperative recovery and related spectra derived from test of hue perception

Abstract: Background Cataract patients were always excluded from studies on ageing of colour vision; thus, effect of age-related cataracts on deterioration of colour perception has not been analysed. In present study, impacts of age-related cataracts on colour discrimination, postoperative recovery and related spectra were investigated. Methods In this cohort study, thirty age-related cataract patients scheduled for binocular surgery and 30 elderly volunteers were enrolled. Colou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…This finding is similar to previous studies using quantitatively discrete and continuous assays. 1 , 2 There is some ambiguity as to whether yellow IOLs cause noticeable tritan deficits. Although earlier versions of blue-blocking IOLs have been shown to induce tritan color defects, 29 other studies have shown no significant difference in color vision under photopic and scotopic light conditions between blue light-filtering IOLs and UV light filtering IOLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is similar to previous studies using quantitatively discrete and continuous assays. 1 , 2 There is some ambiguity as to whether yellow IOLs cause noticeable tritan deficits. Although earlier versions of blue-blocking IOLs have been shown to induce tritan color defects, 29 other studies have shown no significant difference in color vision under photopic and scotopic light conditions between blue light-filtering IOLs and UV light filtering IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Color vision is an integral part of visual function that gradually decreases with age. 1 3 However, visual fields and acuity are the only elements routinely measured or considered in clinical trials. Senescent changes, including senile miosis and increased density and opacity of optical media, 2 , 4 diminish the amount of light reaching the retina where visual transduction initiates visual acuity, contrast sensitivity, and color vision.…”
Section: Introductionmentioning
confidence: 99%
“…Color vision has been shown to be reduced in patients with cataracts. 8,9 However, in this patient's case, only blue color vision returned to normal following cataract surgery. Red and green color discrimination was significantly impaired 1.5 months following cataract extraction, and green color discrimination remained significantly impaired for more than 1 year post cataract surgery.…”
Section: Discussionmentioning
confidence: 58%
“… 7 Cataractous lenses decrease the sensitivity threshold of all three cone classes due to increased scatter and decreased transmittance of visible light, 8 11 with the greatest impact on short-wavelength cones, especially after the age of 60. 11 , 12 Because of this effect, Fujikawa et al 13 established that CCT can be used reliably up to the seventh decade of life and after cataract surgery in elderly patients. Cataractous lenses and posterior capsular opacification 14 also diminish retinal sensitivity measurements obtained using microperimetry.…”
Section: Introductionmentioning
confidence: 99%